Perlindungan Hukum Pencipta Musik Pada Penghimpunan Dan Pendistribusian Royalti Platform Digital Spotify - Rafi Faturahman; Budi Agus Riswandi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is motivated by the reality that the use of music and songs on the Spotify digital platform is utilized by irresponsible people by pirating. The problem in this study is, first, how is the legal protection of the creators of the collection and distribution of royalties for Spotify digital platform music works. Second, what are the legal remedies if there is no legal protection for the creators of Spotify digital platform royalty collection and distribution This research is a type of normative research. The approach used in this research is sociological. The object of research in this study is the legal protection of creators of musical works on the Spotify digital platform, along with legal efforts. The subject of this research is Bagus Rian as a musician or songwriter on the Spotify digital platform. The data sources used in this research are primary data sources supported by secondary data sources. The data collection techniques used in this research are interviews, document studies, and literature studies. This research uses qualitative juridical analysis. The results of this study state that the legal protection of music and song creators on the collection and distribution of Spotify's digital platform only removes pirated music and song content. The Spotify digital platform has no special provisions or mechanisms related to the economic rights of music creators. The arrangements on Spotify's digital platform are also not in line with the ideals of Indonesian laws and regulations regarding the collection and distribution of royalties.